(untitled) (Journal of Economic Research & Business Administration, 2024)
At present, almost every state attracts external loans and credits, which ultimately form an external debt or external debt. The study of this work on external debts of the Republic of Kazakhstan is one of the most important tasks of the monetary policy of the National Bank, in which the emphasis is on assessing trends in the development of external debt, forming a linear model for assessing external debt, obtaining and forecasting the development of external debt based on the obtained models and drafting proposals for reducing external debt. In the work I used the sampling method, analysis of macroeconomic indicators, correlation and regression statistics. As a result of the resulting linear equation, there is an increasing trend in the growth of external debt, which is based on the macroeconomic parameters of GDP, repayment of external debt, exports of goods and services. For the current study, three scenarios for the development of external debt for 2023 were made. At the same time, the main parameter influencing the change in external debt is the export of goods and services. It is clear that the use of natural resources in the structure of exports will not allow it to increase at a rapid pace. Therefore, there is a need to increase the export of goods and services should be carried out through the industrial production of high-quality goods. Considering this, the Republic of Kazakhstan should invest the received loans and loans in industrial technologies that will increase the export of goods. Key words: external debt, external debt assessment, external debt assessment model, Republic of Kazakhstan, forecast of external debt growth.